ANALISIS PENGGUNAAN APLIKASI WORDWALL SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF DALAM PEMBELAJARAN IPA - Ristiani, Ria; Yuliana, Chelsi; Rusli, Tiffany Shahnaz (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted at SD Inpres Koya Tengah as part of fulfiling the Tridharma of higher education by lecturers. The primary aim of this research is to enhance teachers skills utilizing teaching media, particularly in the subject of Science. Currently, teachers at SD Inpres Koya Tengah have limited experience with teaching media and rely heavily on teacher-centered instructional methods. To address this issue, the study focuses on using the Wordwall application as an interactive teaching medium, which is expected to engage students directly and make classroom learning more interactive. The research employs a qualitative descriptive method, with data collection techniques including students satisfaction questionnaires, observation, and documentation. Data analysis detailed and in-depth description, including data collection, sorting, classification, and qualitative interpretation. The anticipated results of this research include improved student interactivity in Science lessons through the use of the Wordwall application for various subjects and materials, thereby enhancing the overall quality of classroom instruction.